2022
DOI: 10.3390/ijms23179794
|View full text |Cite
|
Sign up to set email alerts
|

Study of Thermal Properties, Molecular Dynamics, and Physical Stability of Etoricoxib Mixtures with Octaacetylmaltose near the Glass Transition

Abstract: In this paper, we thoroughly investigated the physical stability of the anti-inflammatory drug etoricoxib, which has been reported earlier to be resistant to recrystallization in its glassy and supercooled states at ambient pressure. Our unique application of the standard refractometry technique showed that the supercooled liquid of the drug was able to recrystallize during isothermal experiments in atmospheric conditions. This enabled us to determine the crystallization onset timescale and nucleation energy b… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(7 citation statements)
references
References 46 publications
0
2
0
Order By: Relevance
“…However, we obtained the same values of m for all compounds despite the fact that they were characterized by completely different degrees of physical stability, which enabled their classification into classes I, II, and III of crystallization tendency. This is an important result because this is another example of the idea that dynamic fragility derived from dielectric measurements of the global molecular dynamics in terms of Equation (2) does not always correctly predict physical stability, even for materials that have remarkably similar molecular structures [ 10 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we obtained the same values of m for all compounds despite the fact that they were characterized by completely different degrees of physical stability, which enabled their classification into classes I, II, and III of crystallization tendency. This is an important result because this is another example of the idea that dynamic fragility derived from dielectric measurements of the global molecular dynamics in terms of Equation (2) does not always correctly predict physical stability, even for materials that have remarkably similar molecular structures [ 10 , 43 , 44 ].…”
Section: Resultsmentioning
confidence: 99%
“…However, recent experimental studies devoted to amorphous materials have indicated some exceptions regarding the suggested correlation between fragility and tendency to crystallize for pure drugs, as well as pharmaceutical compositions [ 10 , 38 , 39 , 40 , 41 , 42 , 43 , 44 ]. Lately, some interesting reports have been published [ 45 , 46 , 47 ] on crystallization kinetics and inter-conformer relaxation dynamics, invoking discussion about the dynamic fragility parameter that does also not reflect the crystallization properties of materials characterized by similar chemical structures.…”
Section: Introductionmentioning
confidence: 99%
“…Within the scope of amorphous pharmaceuticals, we reported on the physical instability of the anti-inflammatory drug etoricoxib [9], which was earlier unexpected, at least in atmospheric conditions. All previous BDS and DSC investigations suggested a very high resistance of the drug to recrystallization from both the supercooled liquid and glassy states at ambient pressure.…”
mentioning
confidence: 78%
“…This Special Issue includes a communication [5] paper and a review [6] devoted to new experimental ideas as well as regular articles [7][8][9] that report the specific molecular properties of materials near the glass transition, which enhance our understanding of molecular mechanisms that may result in contemporary pharmaceutical or other applications. After many years of tests and challenging considerations completed due to the team leader's great research experience in the fields of dielectric and infrared spectroscopies, Kremer et al [5] showed that it is possible to usefully combine those important measurement techniques.…”
mentioning
confidence: 99%
See 1 more Smart Citation